Music-induced cortical plasticity and lateral inhibition in the human auditory cortex as foundations for tonal tinnitus treatment - Pantev, Christo; Okamoto, Hidehiko; Teismann, Henning (Frontiers in Systems Neuroscience, 2012)
Over the past 15 years, we have studied plasticity in the human auditory cortex by means of magnetoencephalography (MEG). Two main topics nurtured our curiosity: the effects of musical training on plasticity in the auditory system, and the effects of lateral inhibition. One of our plasticity studies found that listening to notched music for three hours inhibited the neuronal activity in the auditory cortex that corresponded to the center-frequency of the notch, suggesting suppression of neural activity by lateral inhibition. Crucially, the overall effects of lateral inhibition on human auditory cortical activity were stronger than the habituation effects. Based on these results we developed a novel treatment strategy for tonal tinnitus - tailor-made notched music training (TMNMT). By notching the music energy spectrum around the individual tinnitus frequency, we intended to attract lateral inhibition to auditory neurons involved in tinnitus perception. So far, the training strategy has been evaluated in two studies. The results of the initial long-term controlled study (12 months) supported the validity of the treatment concept: subjective tinnitus loudness and annoyance were significantly reduced after TMNMT but not when notching spared the tinnitus frequencies. Correspondingly, tinnitus-related auditory evoked fields (AEFs) were significantly reduced after training. The subsequent short-term (5 days) training study indicated that training was more effective in the case of tinnitus frequencies ≤ 8 kHz compared to tinnitus frequencies > 8 kHz, and that training should be employed over a long-term in order to induce more persistent effects. Further development and evaluation of TMNMT therapy are planned. A goal is to transfer this novel, completely non-invasive, and low-cost treatment approach for tonal tinnitus into routine clinical practice.